The effect of (TABATA) exercises on some motor abilities and the performance level of the tapping skill for junior basketball players. (Journal of the College of Basic Education, 2022)
The importance of applying Tabata exercises was demonstrated, one of the proposed high-intensity intermittent training (HIIT) methods based on the performance of training intensity that depends on doing intense, rapid and repetitive exercises in a short time and taking quick rest intervals between these exercises, and it has effective effects on the system of motor abilities and the level of movement and The performance of the bourse skill. The researcher has used the experimental method for one experimental group on a sample of (7) players from the Karkh 2 education team. The research sample was chosen by random method. The researcher conducted pre- tests, which are to test the motion abilities and the level of performance of the Tabtaba skill, and then apply the suggested Tabata exercises proposes . For a period of (8) weeks with two units per week and through collecting the results, to the researcher reached the following conclusions: The adoption of TABATA exercises works on developing some of the motion abilities and the skill of plump among junior basketball players, and the researcher recommended the necessity of generalizing this type of exercises.